2014
DOI: 10.1038/nn.3670
|View full text |Cite
|
Sign up to set email alerts
|

G9a influences neuronal subtype specification in striatum

Abstract: Cocaine-mediated repression of the histone methyltransferase (HMT) G9a has recently been implicated in transcriptional, morphological, and behavioral responses to chronic cocaine administration. Here, using a ribosomal affinity purification approach, we find that G9a repression by cocaine occurs in both Drd1 (striatonigral)- and Drd2 (striatopallidal)-expressing medium spiny neurons (MSNs). Conditional knockout and overexpression of G9a within these distinct cell types, however, reveals divergent behavioral ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 35 publications
8
78
0
Order By: Relevance
“…We extended our genetic analysis of m109 to other common AD susceptibility variants 4 which, in earlier studies, displayed very little or no association with neuropathologic features of AD 32,33 . The 21 common AD variants did not associate with m109 (i.e., trans-eQTL analysis), consistent with the observed sparsity of trans-associations (trans-eQTLs) reported in studies with larger sample sizes 34 .…”
Section: Relation Of Rna Derived Modules To the Genetic Architecture supporting
confidence: 84%
“…We extended our genetic analysis of m109 to other common AD susceptibility variants 4 which, in earlier studies, displayed very little or no association with neuropathologic features of AD 32,33 . The 21 common AD variants did not associate with m109 (i.e., trans-eQTL analysis), consistent with the observed sparsity of trans-associations (trans-eQTLs) reported in studies with larger sample sizes 34 .…”
Section: Relation Of Rna Derived Modules To the Genetic Architecture supporting
confidence: 84%
“…Although we found that the number of Foxp1 target genes is roughly equally distributed between genes enriched in both D 1 + and D 2 + MSNs (Fig. 2D), the number of Foxp2 target genes enriched in D 1 + MSNs is almost twice the number of Foxp2 target genes enriched in D 2 + MSNs (Heiman et al 2008;Vernes et al 2011;Maze et al 2014). These results are in line with published data showing that Foxp2 is more enriched in D 1 + MSNs.…”
Section: Foxp1 Regulates Shared Targets With Foxp2 In the Striatummentioning
confidence: 77%
“…in the coordination of motor activity (Gerfen and Surmeier 2011 (Maze et al 2014). We found a significant enrichment of both Foxp1 and Foxp2 target genes within D 1 + MSNs specifically (Fig.…”
Section: Foxp1 Regulates Shared Targets With Foxp2 In the Striatummentioning
confidence: 99%
“…Although well beyond the scope of the current study, it will be necessary in the future to investigate the contributions of these numerous cell types to transcriptional, synaptic, and behavioral abnormalities observed following CSDS. Indeed, previous work has already provided a wealth of data demonstrating that distinct cell types and circuits in striatum are segregated, both molecularly and electrophysiologically, in their responses to chronic stress, thereby contributing differentially to distinct phenotypes observed across numerous psychiatric disease models (22,23).…”
mentioning
confidence: 99%